HUBUNGAN INTENSITAS DAN POLA PENGGUNAAN MEDIA SOSIAL (TIKTOK) DENGAN STABILITAS EMOSI MAHASISWA TINGKAT AKHIR PADA MASA DEWASA AWAL - Ariyanto, Catherine Dian Asmarani Putri; Conia, Putri Dian Dia; Afiati, Evi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the relationship between the intensity and patterns of TikTok social media use and emotional stability among final-year university students in early adulthood. This study employed a quantitative approach with a correlational method. The sample consisted of 123 final-year students from the Faculty of Teacher Training and Education, Universitas Sultan Ageng Tirtayasa, selected using purposive sampling. Data were collected using Likert scales measuring the intensity and patterns of TikTok use based on frequency, duration, passive exposure through the For You Page (FYP), and active searching through the search bar, as well as emotional stability based on optimism, empathy, independence (autonomy), calmness, and tolerance. Data were analyzed using descriptive analysis and Spearman’s rank correlation. The results showed that the majority of respondents had a moderate level of TikTok use intensity and patterns, with 87 respondents (70.7%), while emotional stability was also predominantly in the moderate category, with 91 respondents (74%). The Spearman’s rank correlation test yielded a correlation coefficient of -0.127 with a significance value of 0.161 (p > 0.05), indicating a negative, very weak, and statistically non-significant relationship. Therefore, there is no significant relationship between the intensity and patterns of TikTok social media use and emotional stability among final-year university students in early adulthood.